2015
DOI: 10.1183/16000617.00006614
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the management and treatment of pulmonary embolism

Abstract: Pulmonary embolism (PE) is a serious and costly disease for patients and healthcare systems. Guidelines emphasise the importance of differentiating between patients who are at high risk of mortality (those with shock and/or hypotension), who may be candidates for thrombolytic therapy or surgery, and those with less severe presentations. Recent clinical studies and guidelines have focused particularly on risk stratification of intermediate-risk patients. Although the use of thrombolysis has been investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 83 publications
1
19
0
Order By: Relevance
“…23 Our study confirmed that in patients with unprovoked PE, the risk of recurrence is markedly higher than in those with provoked VTE, which agrees with other studies. 24 Elevated D-dimer after anticoagulation withdrawal also predicted PE recurrence in our study like in many others. 5,6,18,19 Elevated CRP, indicating enhanced systemic inflammation, has been shown in patients at risk of VTE 25 ; however, we did not observe higher CRP in subjects with recurrent PE.…”
Section: Discussionsupporting
confidence: 88%
“…23 Our study confirmed that in patients with unprovoked PE, the risk of recurrence is markedly higher than in those with provoked VTE, which agrees with other studies. 24 Elevated D-dimer after anticoagulation withdrawal also predicted PE recurrence in our study like in many others. 5,6,18,19 Elevated CRP, indicating enhanced systemic inflammation, has been shown in patients at risk of VTE 25 ; however, we did not observe higher CRP in subjects with recurrent PE.…”
Section: Discussionsupporting
confidence: 88%
“…The mortality rate in APE differs from >15% in haemodynamically unstable patients, 3-15% in intermediate risk patients with right ventricular dysfunction or myocardial damage and <1% in low risk patients (18). This indicates the importance of distinguishing the relatively small group of haemodynamically unstable high-risk patients from the normotensive intermediate-or low-risk patients (18,19).…”
Section: Apementioning
confidence: 98%
“…[4] The combination of clinical probability estimation, CTPA, and serum D-dimer levels is usually used to establish the diagnosis. [5] Dyspnea, tachypnea, chest pain, cough, hemoptysis, tachycardia, syncope, and respiratory crepitations are common symptoms of PE, but none of these is unique to the condition.…”
Section: Resultsmentioning
confidence: 99%
“…Syncope or near syncope, hypotension, extreme hypoxemia, electromechanical dissociation , or cardiac arrest is suggestive of a massive PE. [4] Pulmonary embolism is a potentially fatal condition if left untreated. [6,7] Its presentation can be relatively mild, sometimes even mimicking myalgia or a simple cough.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation